FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI SEDIAAN GEL HAND SANITIZER EKSTRAK ETANOL DAUN BAYAM MERAH (Amaranthus Tricolor L.) TERHADAP BAKTERI Staphylococcus aureus & Eschericia coli - Zola Efa Harnis (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
Red spinach has function as skin antiseptic. It has antibacterial activity because it contains compounds such as tannins, flavonoids, saponins, and steroids. The purpose of formulation and test of antibacterial activity of hand sanitizer gel preparation red spinach extract and evaluation of physical quality of hand sanitizer. Antibacterial activity test was measured by diffusion method using paper disk to measuring the diameter of the bacterial growth inhibition zone of Escherichia coli and Staphylococcus aureus. Concentration extract ethanol of leaf red spinach (and formula of hand sanitizer gel used (F1) blanco; (F2) 5%; (F3) 10%; (F4) 20% and (F5) control positive/detol. Evaluation of physical properties of hand sanitizer gel include of: homogeneity test, stability test and pH test. The results has found showed that antibacterial activity test of gel extract leaves red spinach (on Escherichia coli inhibited at without extract/blanco was 0 mm, concentration of 5% with diameter of inhibit was 14,99 mm, concentration of 10% with diameter of inhibit was 17,26 mm, concentration of 20% with diameter of inhibit was 18,26 mm and using control positive was 19.33. And then for bacteri Staphylococcus aures at concentration of without extract/blanco was 0 mm, 5% with diameter of inhibit was 15,5 mm, concentration of 10% with diameter of inhibit was 15,96 mm and concentration of 20% with diameter of inhibit was 17,43 mm and using control positive was 18.33 mm. So we can conclude that hand sanitizer gel of leaf red spinach have less inhibited growth against Escherichia coli and Staphylococcus aureus.